Constructing Professional Identity: The Role of Work and Identity Learning Cycles in the Customization of Identity Among Medical Residents - Pratt, Michael G.; Rockmann, Kevin W.; Kaufmann, Jeffrey B. (Academy of Management Journal, 2006)
Through a six-year qualitative study of medical residents, we build theory about professional identity construction. We found that identity construction was triggered by work-identity integrity violations: an experienced mismatch between what physicians did and who they were. These violations were resolved through identity customization processes (enriching, patching, or splinting), which were part of interrelated identity and work learning cycles. Implications of our findings (e.g., for member identification) for both theory and practice are discussed.